2020
DOI: 10.1113/ep088686
|View full text |Cite
|
Sign up to set email alerts
|

Chronic antioxidant administration restores macrovascular function in patients with heart failure with reduced ejection fraction

Abstract: Heart failure with reduced ejection fraction (HFrEF) is characterized by macrovascular dysfunction and elevated oxidative stress that may be mitigated by antioxidant (AOx) administration. In this prospective study, we assessed flow-mediated dilatation (FMD) and reactive hyperaemia responses in 14 healthy, older control participants and 14 patients with HFrEF, followed by 30 days of oral AOx administration (1 g vitamin C, 600 I.U. vitamin E and 0.6 g α-lipoic acid) in the patient group. Blood biomarkers of oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The second study of HFrEF patients was characterized by macrovascular endothelial dysfunction, which may be due, at least in part, to a change in redox balance, leading to increased oxidative stress and decreased endogenous AOx protection. The results of this small study showed that chronic AOx administration is a simple way to improve macrovascular function, reduce oxidative stress, and increase AOx capacity in patients with HFrEF [221] (Table 2). However, larger sample studies are needed to properly investigate the beneficial effects of this compound.…”
Section: Antioxidantsmentioning
confidence: 93%
See 1 more Smart Citation
“…The second study of HFrEF patients was characterized by macrovascular endothelial dysfunction, which may be due, at least in part, to a change in redox balance, leading to increased oxidative stress and decreased endogenous AOx protection. The results of this small study showed that chronic AOx administration is a simple way to improve macrovascular function, reduce oxidative stress, and increase AOx capacity in patients with HFrEF [221] (Table 2). However, larger sample studies are needed to properly investigate the beneficial effects of this compound.…”
Section: Antioxidantsmentioning
confidence: 93%
“…Vitamin-antioxidants, Mito-TENPO, enzyme-scavengers of ROS and elamipretide were investigated (Table 2). Some small studies evaluated vitamin-antioxidants combinations in HFpEF [216] and HFrEF [221] and discovered improvement in peripheral vascular function and decrease in oxidative stress (Table 2). In the first study, reactive hyperemia (RH), a measure of microvascular function, did not change after OC (combination of α-lipoic acid, vitamin C and vitamin E) administration.…”
Section: Antioxidantsmentioning
confidence: 99%
“…Sacubitril/valsartan downregulates the expression of proinflammatory cytokines IL-6, IL-1α, tumor necrosis factor (TNFβ), chemokine (MCP-1), and chemokine CXC motif ligand-1 (CXCL1) by inhibiting the Toll-like receptor 4 (TLR4)/myeloid differentiation factor 88 (Myd88) pathway, NF-κB p65 nuclear translocation, and improving lipopolysaccharide (LPS)-induced endothelial cell inflammation (20). It significantly reduces circulating TNF-α and IL-18 levels in patients with HF with reduced ejection fraction (HFrEF) after 4 weeks of treatment, accompanied by improved peripheral vascular function and increased exercise tolerance (21).…”
Section: Mechanisms Of Action Of Sacubitril Valsartan: Experimental E...mentioning
confidence: 99%
“…Antioxidant supplementation comprising vitamin C (1 g), vitamin E (600 I.U. ), and α-lipoic acid (0.6 g) for 30 days exerted beneficial effects on macrovascular function in patients with HFrEF ( Bunsawat et al, 2020 ). A recent meta-analysis also revealed that vitamin C administration augmented LVEF in heart failure patients ( Hemilä et al, 2022 ).…”
Section: Mechanistic Roles Of Sacubitril/valsartan In Cardiac Remodelingmentioning
confidence: 99%